2018
DOI: 10.1093/jas/sky147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of roller mill configuration on growth performance of nursery and finishing pigs and milling characteristics1

Abstract: Three experiments were conducted to evaluate the effects of roller mill configuration on growth performance of nursery and finishing pigs, feed preference, and feed mill throughput. The four experimental treatments included corn ground through a roller mill using two, three, four sets of rolls in a fine-grind configuration, or four sets of rolls in a coarse grind configuration. The same roller mill was used for all configurations with the appropriate lower rolls completely open when using the two or three roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…The increase in grinding intensity obtained by reducing the screen hole diameter (screen used to surround the grinding chamber in hammer mill) makes it difficult for the corn to leave the crushing chamber in the grain process, with a consequent greater number of hammer impacts on the corn particles, which leads to reduced PS and GSD (Table 2). This reduction in GSD with the reduction in PS is a relatively common behavior and has already been reported by Paiano et al (2014); Rojas and Stein (2015); Chiodelli, Folador, Boiago, Carvalho, and Paiano (2018) and Gebhardt et al (2018); said behavior is associated with grain reprocessing, which is characterized by reduced particle size variability.…”
Section: Feed and Diets Characteristicssupporting
confidence: 62%
See 2 more Smart Citations
“…The increase in grinding intensity obtained by reducing the screen hole diameter (screen used to surround the grinding chamber in hammer mill) makes it difficult for the corn to leave the crushing chamber in the grain process, with a consequent greater number of hammer impacts on the corn particles, which leads to reduced PS and GSD (Table 2). This reduction in GSD with the reduction in PS is a relatively common behavior and has already been reported by Paiano et al (2014); Rojas and Stein (2015); Chiodelli, Folador, Boiago, Carvalho, and Paiano (2018) and Gebhardt et al (2018); said behavior is associated with grain reprocessing, which is characterized by reduced particle size variability.…”
Section: Feed and Diets Characteristicssupporting
confidence: 62%
“…Some studies such as the one carried out by Ball et al (2015), which characterized feeds as finely or coarsely ground, did not observe any effect on these variables in the finishing phase. Likewise, Gebhardt et al (2018), in a study of corn ground in a roller mill, with PS ranging between 267 and 525 µm, did not verify any effect on DFI and DWG for piglets in the nursery phase. However, Huang et al (2015), in a study with weaned piglets, detected an improvement in DFI and DWG with increasing corn grinding intensity (PS reduction from 405 to 285 µm), and Gebhardt et al (2018) found negative effects on intake and gain in the finishing phase of swine, with a PS reduction from 561 to 285 µm.…”
Section: Zootechnical Performancementioning
confidence: 90%
See 1 more Smart Citation
“…Samples were analyzed both with (5 g) and without a dispersing agent (Gilson Company, Inc., Lewis Center, OH) using two separate stainless-steel sieve stacks (13 sieves each) to prevent residual dispersing agent from affecting results. Both sieve stacks contained agitators and were placed in the Ro-Tap (Model RX-29, W. S. Tyler Industrial Group, Mentor, OH) machine for 15 min, using the same sieve and agitator configurations as Gebhardt et al (2018) .…”
Section: Methodsmentioning
confidence: 99%
“…Pigs prefer course ground corn and pellets with a larger diameter. 20,36,37 In pens where lightweight or removal pigs are housed, an intensive care diet with highly palatable ingredients may need to be provided before the starter diet to encourage earlier feed intake.…”
Section: Intensive Care Pen Managementmentioning
confidence: 99%